Zoroastrian Rituals in Context. - Michael Stausberg (Editor) (Numen Book Series, 2004)
Rituals, it is agreed, play a prominent role in Zoroastrianism, one of the oldest continuous traditions of mankind. In this book, scholars from a broad range of disciplines make the first ever collective effort to address this issue. From a historical and geographical perspective, texts and contexts studied in these pages range from antiquity to modernity, all the way from Japan, China, India, Iran, Europe to California. The essays touch on questions of theory, ritual texts, change and performances, gender and professional religion (priesthood/lay-people). The rituals studied are placed in a broad scope of social and local settings ranging from the royal court to the needy, from the rural village to the urban metropolis, from the domestic to the public.